2019
DOI: 10.1016/j.jcol.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Congenital abnormalities and anatomical variations of the vermiform appendix and mesoappendix

Abstract: Aim  The purpose of this review was to present and discuss the anatomical variations and congenital abnormalities of the vermiform appendix and mesoappendix reported in recent years, and their associations with acute appendicitis and other associated pathologies. Methods  The search was carried out in the following databases: PubMed, Science Direct, and SciELO. Results  Thirty-seven studies were included in this review. Among the abnormalities of the vermiform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 32 publications
2
35
0
Order By: Relevance
“… 4 , 15 Intestinal malformations, dextrocardia, hexadactylism and congenital cataract are also mentioned as associated conditions, which are absent in our patient. 4 , 5 , 8…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“… 4 , 15 Intestinal malformations, dextrocardia, hexadactylism and congenital cataract are also mentioned as associated conditions, which are absent in our patient. 4 , 5 , 8…”
Section: Discussionmentioning
confidence: 52%
“…The diagnosis can be challenging if the presentation is atypical and this may result in treatment delay. 4 , 11 , 12 Alvarado score is the most widely used scoring system in the clinical diagnosis of this condition. A systematic review done by Ohle et al reported Alvarado score as an accurate diagnostic “rule out” score at a cut point 5 for all patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous case reports the patient had undergone appendicectomy on two occasions which can give rise to significant morbidity and mortality [3]. In selected cases, the caecum should be carefully examined for appendices anomalies [4]. To the best of our knowledge, this is the 1st case reported from Sri Lanka.…”
Section: The Cave Wall Bridge Classification [2]mentioning
confidence: 88%